2009
DOI: 10.1001/archgenpsychiatry.2009.58
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse-Translational Study of Dysfunctional Exploration in Psychiatric Disorders

Abstract: Context Bipolar mania and schizophrenia are recognized as separate disorders but share many commonalities, raising the question of whether they are in fact the same disorder on different ends of a continuum. The lack of distinct endophenotypes of bipolar mania and schizophrenia has complicated the development of animal models that are specific to these disorders. Exploration is fundamental to survival and is dysregulated in these two disorders. Although exploratory behavior in rodents has been widely studied, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
280
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(315 citation statements)
references
References 56 publications
31
280
3
1
Order By: Relevance
“…Although impaired decision making of the reduced DAT model animals here could therefore resemble other clinical populations, the consistencies of BD patient IGT performance including the sensitivity for rewards, to our reduced DAT functioning in mice are striking. These findings are reinforced by previous observations of parallels between behavior of these DAT models and that of BD patients in other paradigms (Henry et al, 2013;Perry et al, 2009;van Enkhuizen et al, 2012). Moreover, supporting the increased reward-seeking trait of DAT KD mice, chronic DAT reduction also resulted in faster reaction times, fewer omissions, and increased premature responses in both the present and previous studies (Young et al, 2011).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although impaired decision making of the reduced DAT model animals here could therefore resemble other clinical populations, the consistencies of BD patient IGT performance including the sensitivity for rewards, to our reduced DAT functioning in mice are striking. These findings are reinforced by previous observations of parallels between behavior of these DAT models and that of BD patients in other paradigms (Henry et al, 2013;Perry et al, 2009;van Enkhuizen et al, 2012). Moreover, supporting the increased reward-seeking trait of DAT KD mice, chronic DAT reduction also resulted in faster reaction times, fewer omissions, and increased premature responses in both the present and previous studies (Young et al, 2011).…”
Section: Discussionsupporting
confidence: 73%
“…Previously, we reported that mice with reduced DAT functioning mimicked abnormal behaviors of BD mania patients (Perry et al, 2009). Mice that are hyperdopaminergic via genetic DAT knockdown (KD; Zhuang et al, 2001) or pharmacological DAT inhibition (GBR12909 treatment) exhibited this profile.…”
Section: Introductionmentioning
confidence: 86%
“…Mice with constitutive genetic knockdown of DAT (DAT-KD) express 10% of wild-type (WT) DAT levels and also show high DA levels. They display mania-like behaviors such as hyperactivity in a novel environment (Zhuang et al, 2001), replicating hyper-exploration and increased risk-taking behavior of manic BD patients (Perry et al, 2009;van Enkhuizen et al, 2014;Young et al, 2011b) without concomitant developmental defect. For these reasons, DAT-KD mice have been used as a model for mania.…”
Section: Introductionmentioning
confidence: 97%
“…understand its pathophysiology and to develop new treatments for the condition (22)(23)(24)(25). In two previous studies, Shank2 mice bearing deletions of exon 6 or exons 6-7 displayed autism-like behaviors and cognitive impairment (26,27).…”
Section: Introductionmentioning
confidence: 99%